2007
DOI: 10.3727/000000007783464876
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3Increases the Transplantation Success of Human Muscle Precursor Cells in SCID Mice

Abstract: Human muscle precursor cell (hMPC) transplantation is a potential therapy for severe muscle trauma or myopathies. Some previous studies demonstrated that 1,25-dihydroxyvitamin-D 3 (1,25-D 3 ) acted directly on myoblasts, regulating their proliferation and fusion. 1,25-D 3 is also involved in apoptosis modulation of other cell types and may thus contribute to protect the transplanted hMPCs. We have therefore investigated whether 1,25-D 3 could improve the hMPC graft success. The 1,25-D 3 effects on hMPC prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…32 Also, it has been reported that D3 enhances grafting of human muscle precursor cells (hMPCs) into muscle after transplantation into SCID mice. 33 The authors suggested that D3 increase proliferation and differentiation of hMPCs and that this would explain the transplantation improvement. Our present results suggest that the improvement could be due to an increase of dysferlin expression after treatment of hMPCs with D3.…”
Section: Discussionmentioning
confidence: 98%
“…32 Also, it has been reported that D3 enhances grafting of human muscle precursor cells (hMPCs) into muscle after transplantation into SCID mice. 33 The authors suggested that D3 increase proliferation and differentiation of hMPCs and that this would explain the transplantation improvement. Our present results suggest that the improvement could be due to an increase of dysferlin expression after treatment of hMPCs with D3.…”
Section: Discussionmentioning
confidence: 98%
“…Its success relies on the incorporation of these cells into regenerating myofibers. Progenitor cells derived from both skeletal muscle (34,49,55,57) as well as from other tissues (1,13, 21,52,59) have been explored for this purpose (6,44,47). Although experimental and clinical studies with myoblasts have yielded important insights, their clinical application is hampered by (i) limited availability, (ii) restricted ex vivo proliferation capacity, and (iii) limited spread in host muscles (45,56,60).…”
Section: Introductionmentioning
confidence: 99%